PURIFICATION AND CHARACTERIZATION OF AN ANTIOXIDANT METALLOENZYME FROM LOCAL TOMATO VARIETY. - Maqsood, Beenish; Iqbal, Tehmina; Nadeem, Syeda Kamila; Saleem, Mahjabeen; Iqbal, Afshan; Hussain, Ferhana (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
The isolation, purification and characterization of an antioxidant enzyme superoxide dismutase (SOD), from local tomato variety, has been reported in this study. Whole tomato extracts from different ripening stages were prepared in chilled 0.01M citrate phosphate buffer (pH 7.0) containing protease inhibitor. SOD activity along with total protein content at various stages of maturity and ripening were correlated. The rotten tomato sample, showing highest specific activity i.e. 140 IU/mg was selected for further purification and was subjected to 80% ammonium sulfate precipitation. Precipitated proteins were dialyzed and loaded to sephadex G-75 column for gel filtration chromatography. The enzyme was purified up to 6 fold with a final specific activity of 825 IU/mg with a 40.4 % yield. The PAGE analysis of purified sample under denaturing conditions showed a single band of 16 KDa. The purified enzyme was thermally stable under mesophilic conditions i.e. up to 40°C and was most stable between acidic to neutral pH values 5.0-7.0. Based on atomic absorption spectroscopic analysis and sensitivity to inhibitors such as urea, H2O2, chloroform-ethanol and KCN, the enzyme was found to be Fe-SOD.